Study Comparative Stability of Dam Body with Geomembrane Core Material using GeoStudio Application - Unicolas Satria Oktavianus Nainggolan; Tika Ermita Wulandari (LPPM Universitas Andalas, 2024)
The availability of embankment material and the quality of the material is one of the problems in planning a dam, especially impermeable material which must be watertight. With the GeoStudio application, the dam will be modeled to observe the stability of the dam, especially against landslides and seepage. Modeling I is modeled with core zone material using upstream borrow clay material and modeling II using downstream borrow clay material. Modeling III and IV used the same core material with the addition geomembrane material between the transition zone and the upstream filter. The geomembrane was added to observe and compare the effect of use on the stability. The weir body was analyzed under conditions when the weir body was completed, flood water level, normal water level, low water level and rapid drawndown water condition. Modeling III with upstream borrow clay material and geomembrane between the transition zone and upstream filter is the design with the best stability with the most critical avalanche safety factor of 2.459 downstream of the weir under flood water level conditions. The seepage discharge downstream of the weir is 0.0017 m³/dt/m and the maximum seepage discharge is 0.0026 m³/dt/m under flood water level conditions.